PENGEMBANGAN E-BOOK PUISI MATEMATIKA PADA MATA PELAJARAN MATEMATIKA SMP - Mumtazah, Nadia Wardah; Bistari, Bistari; Hartoyo, Agung (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Mathematical poetry is considered capable of developing a culture of reading, writing, and arithmetic in the process of learning mathematics. This study aims to identify and describe the development process and the quality of the results of the development of a mathematical poetry e-book. To achieve this, the research and development (R&D) method with the 4D model (define, design, develop, and disseminate) is applied without carrying out the fourth stage. The development process begins with the define stage, which includes analyzing curriculum, needs, and materials as well as developing competency achievement indicators. After that, product prototypes were designed at the design stage, then consulted with three experts as validators at the development stage before being tested on teachers and students to find out their practicality and effectiveness. The findings of this study include the development of a mathematical poetry e-book in pdf format that is: 1) very valid in terms of material, media, and poetry aspects, with a validity value of 4.56; 2) very practical in terms of ease of use, efficiency of learning time, and benefits of teaching materials, with a practicality value of 4.25; and 3) effective in improving student learning outcomes. Based on the results of this study, it can be concluded that the mathematics poetry e-book in junior high school mathematics as a development product in this study meets the requirements as a quality development product. Nonetheless, a product with new innovations has some advantages and disadvantages.